A Rhizavidin Monomer with Nearly Multimeric Avidin‐Like Binding Stability Against Biotin Conjugates. (2nd February 2016) - Lee, Jeong Min; Kim, Jung A.; Yen, Tzu‐Chi; Lee, In Hwan; Ahn, Byungjun; Lee, Younghoon; Hsieh, Chia‐Lung; Kim, Ho Min; Jung, Yongwon
Abstract: Developing a monomeric form of an avidin‐like protein with highly stable biotin binding properties has been a major challenge in biotin‐avidin linking technology. Here we report a monomeric avidin‐like protein—enhanced monoavidin—with off‐rates almost comparable to those of multimeric avidin proteins against various biotin conjugates. Enhanced monoavidin (eMA) was developed from naturally dimeric rhizavidin by optimally maintaining protein rigidity during monomerization and additionally shielding the bound biotin by diverse engineering of the surface residues. eMA allowed the monovalent and nonperturbing labeling of head‐group‐biotinylated lipids in bilayer membranes. In addition, we fabricated an unprecedented 24‐meric avidin probe by fusing eMA to a multimeric cage protein. The 24‐meric avidin and eMA were utilized to demonstrate how artificial clustering of cell‐surface proteins greatly enhances the internalization rates of assembled proteins on live cells.